Aloe-emodin attenuates hyperuricemia-induced renal injury in mice by mitigating inflammation and oxidative stress - Wang, Shengfeng; Zhu, Quanfeng; Zhang, Chengcheng; Hu, Shuang; Liu, Daqun; Yu, Jiawen; Liu, Xiao; Chen, Yan; Jiang, Guojun (Frontiers in Nutrition, 2025)
BackgroundAloe-emodin (AOE), the principal anthraquinone constituent derived from aloe and rhubarb, exhibits antioxidant and anti-inflammatory properties, suggesting its therapeutic potential against hyperuricemia (HUA) and associated renal injury. Here, we investigated the potential of AOE in mitigating HUA and related kidney damage, with a focus on its underlying biological mechanisms.MethodsA HUA mouse model was established by oral gavage of potassium oxonate (PO, 1.5 g/kg) and adenine (Ad, 0.1 g/kg). Serum uric acid (UA) levels, kidney function indicators, histological changes, inflammatory response, and oxidative stress state were assessed to evaluate the urate-lowering and kidney-protective roles of AOE. Furthermore, transcriptomic profiling and RT-qPCR analysis were employed to investigate how AOE contributes to UA reduction and renal protection.ResultsAOE lowered serum UA levels and inhibited xanthine oxidase and adenosine deaminase activity. Moreover, AOE improved kidney function indicators (reflected by reductions in serum creatinine and blood urea nitrogen levels), restored the integrity of renal tissue structure, and mitigated inflammation and oxidative stress in HUA-exposed animals. Transcriptomic analysis revealed 2,307 differentially expressed key genes associated with AOE against HUA in kidney. Furthermore, AOE downregulated p65/RelA and NF-κB1/p50 transcript levels, while increasing PPARα, PPARγ, and CPT2 expression.ConclusionAOE effectively lowered serum UA levels, and exhibited renal protection in the PO/Ad-induced HUA mouse model by dampening inflammatory signaling and restoring redox equilibrium, likely through the PPAR and NF-κB pathways. This study demonstrated that AOE is a promising natural candidate with a desirable safety profile for treating HUA and renal injury, and more experimental validation are needed in the future.